Frailty assessment instruments in heart failure: A systematic review. (1st January 2018) - McDonagh, Julee; Martin, Lily; Ferguson, Caleb; Jha, Sunita R; Macdonald, Peter S; Davidson, Patricia M; Newton, Phillip J
Abstract: Background: Frailty is an independent predictor of mortality across many conditions. Reported rates of frailty in heart failure range from 15% to 74%. There are several instruments available to assess frailty; however, to date there has been no consensus on the most appropriate instrument for use in individuals with heart failure. Aims: To identify how frailty is assessed in individuals with heart failure and to elucidate which domains of frailty are most frequently assessed. Methods: Key electronic databases were searched (MEDLINE, COCHRANE Central and CINAHL) to identify studies that assessed frailty in individuals with heart failure using a formal frailty instrument. Results: Twenty studies published in 24 articles were included, for which a total of seven unique frailty instruments were identified. The most commonly used instrument was the Frailty Phenotype ( n = 11), with the majority of studies using a modified version of the Frailty Phenotype ( n = 8). The second most commonly used instrument identified was the Comprehensive Geriatric Assessment ( n = 4). Conclusion: There is an increasing interest in the assessment of frailty, but, to date, there is no frailty instrument validated specifically in the heart failure population.